Structurally controlled gold in the Beposo area, Ashanti Region, Ghana: testing a mineral-systems targeting model with random forest and decision tree classifiers - Eric Dominic Forson; Samuel Nunoo; Prince Ofori Amponsah; Ralph Dartey Osei; Patrick Asamoah Sakyi (Earth Science Informatics, 2026)

Spatio-temporal analysis of Ghana’s ecological zones: integrating multispectral remote sensing and machine learning algorithms - Augustine O. K. N. Mensah; Bi Shuoben; Clement Kwang; Emmanuel Yeboah; Isaac Sarfo; Ebenezer Nikoi; Collins Oduro; Prince Martin Gyekye; Ishmeal Quist; Princella Ofori Darko; Clement Issaka Anaba; Asante Vincent Antwi (Environmental Monitoring and Assessment, 2026)

Toward urban wetland sustainability – a multivariate statistical analysis of encroachers' outlook - Akosua Baah Kwarteng Amaka-Otchere; Eric Oduro-Ofori; Otiwaa Boakye; Prince Boakye Frimpong; Kafui Ocloo; John Bosco Dramani (Science of The Total Environment, 2026)

Exploring the intricacies of indoor dust pollution from neonicotinoid insecticides and its human health impacts: An exemplar from eleven agricultural communities in Ghana, West Africa - Collins NIMAKO; Osei AKOTO; Nathaniel BOADI; Prince OFORI; Yared B. YOHANNES; Shouta M.M. NAKAYAMA; Yoshinori IKENAKA; Mayumi ISHIZUKA (Journal of Hazardous Materials, 2025)

Dating multiple fractionation trends in pegmatites – Implications for the genesis of a large lithium pegmatite province in West-Africa - Marieke Van Lichtervelde; Oscar Laurent; Prince Ofori Amponsah; Isaac Iwan E. Williams (Chemical Geology, 2025)

Petrology and geochemistry of the Suhum Basin granitoid complex, Ghana: Implications for crustal growth during the Rhyacian orogeny of the West African Craton - Daniel Kwayisi; Prince Ofori Amponsah; Emmanuel Kwaku Awunyo; Marian Selorm Sapah; Patrick Asamoah Sakyi; Ben-Xun Su; Prosper M. Nude; Abigail Enyonam Ayikwei; Eric Dominic Forson (Journal of African Earth Sciences, 2025)

Interfacial composition on the mechanical properties, microstructure and digestion of emulsion-filled whey protein gels: Effect of soy and whey protein ratios - Georgina Benewaa Yeboah; Sen Wang; Wei Wu; Haowei Zhang; Prince Ofori Donkor; Juan Wu; Yu Cheng (Food Bioscience, 2025)

Effects of foliar selenium, biochar, and pig manure on cadmium accumulation in rice grains and assessment of health risk - Ofori Prince Danso; Zhangmin Wang; Zezhou Zhang; Shanshan Niu; Yuanqi Wang; Gege Wu; Xiaohu Wang; Li Zheng; Jun Dai; Xuebin Yin; Renbin Zhu (Environmental Research, 2024)

Groundwater potential modeling over the eastern part of Ghana’s Northern Region using evidence belief functions and weight of evidence - Eric Dominic Forson; Elikplim Abla Dzikunoo; Prince Ofori Amponsah; Aboagye Menyeh; Samuel Nunoo; Theophilus Yaw Amponsah (Earth Science Informatics, 2024)

A preliminary predictive model for selenium nutritional status in residents based on three selenium biomarkers - Shanshan Niu; Zhangmin Wang; Xuebin Yin; Xiaodong Liu; Liqiang Qin; Muhammad Raza Farooq; Ofori Prince Danso; Zezhou Zhang; Qin Luo; Chenlu Sun; Jiaping Song (Journal of Trace Elements in Medicine and Biology, 2024)

Characterisation and rare-metal potential of the Winneba-Mankoadze pegmatites, Southern Ghana: Evidence of two pegmatite fields - Salaam Jansbaka Adams; Marieke Van Lichtervelde; Prince Ofori Amponsah; Prosper Mackenzie Nude; Daniel Kwadwo Asiedu; Samuel Boakye Dampare (Journal of African Earth Sciences, 2023)

Air‐breathing behavior in Heterotis niloticus fingerlings: Response to changes in oxygen, temperature, and exercise regimes - Henry Owusu Adjei; Robert Yadama Laar; Prince Ofori‐Darkwah; Emmanuel Xorla Xatse; Jedida Osei Bediako; Peter Vilhelm Skov; Kwasi Adu Obirikorang (Journal of Fish Biology, 2023)
Air‐breathing in fish is believed to have arisen as an adaptation to aquatic hypoxia. Although air‐breathing has been widely studied in numerous fish species, little is known about the obligate air‐breathing African bonytongue, Heterotis niloticus . We evaluated if abiotic factors and physical activity affect air‐breathing patterns in fingerlings. The air‐breathing frequency ( f AB ) and behavioral responses of H. niloticus fingerlings were assessed in response to environmental oxygen, temperature, and exhaustion and activity in a series of experiments. The air‐breathing behavior of H. niloticus fingerlings under optimum water conditions was characterized by swift excursions lasting less than 1 s to the air–water interface to gulp air. The intervals between air‐breaths were highly variable, ranging from 3 to 259 s. Body size only slightly affected f AB , while hypoxia, hyperthermia, and exercise stress significantly increased f AB . Progressive hypoxia from 17.69 to 2.17 kPa caused a ~2.5‐fold increase in f AB . Increasing temperatures to 27 and 32°C, from a baseline temperature of 22°C, significantly increased f AB from 0.4 ± 0.2 to 1.3 ± 0.5 and 1.6 ± 0.4 breaths min −1 , respectively. Lastly, following exhaustive exercise, f AB increased up to 3‐fold. These observations suggest that H. niloticus fingerlings are very reliant on aerial oxygen, and their air‐breathing behavior is sensitive to environmental changes and activity levels.

Mineral prospectivity mapping over the Gomoa Area of Ghana's southern Kibi-Winneba belt using support vector machine and naive bayes - Eric Dominic Forson; Prince Ofori Amponsah (Journal of African Earth Sciences, 2023)

Geospatial modelling of mineral potential zones using data-driven based weighting factor and statistical index techniques - Prince Ofori Amponsah; Eric Dominic Forson (Journal of African Earth Sciences, 2023)

Frequency ratio-based flood vulnerability modeling over the greater Accra Region of Ghana - Eric Dominic Forson; Prince Ofori Amponsah; Godfred Bright Hagan; Marian Selorm Sapah (Modeling Earth Systems and Environment, 2023)

Groundwater prospectivity modeling over the Akatsi Districts in the Volta Region of Ghana using the frequency ratio technique - Prince Ofori Amponsah; Eric Dominic Forson; Prospera Sungpour Sungzie; Yvonne Sena Akosuah Loh (Modeling Earth Systems and Environment, 2023)

Paleoproterozoic gold events in the southern West African Craton: review and synopsis - Quentin Masurel; Aurélien Eglinger; Nicolas Thébaud; Andrew Allibone; Anne-Sylvie André-Mayer; Helen McFarlane; John Miller; Mark Jessell; Laurent Aillères; Olivier Vanderhaeghe; Stefano Salvi; Lenka Baratoux; et al. (Mineralium Deposita, 2022)